Métodos de estruturação de problemas: uma revisão de literatura - Batista, Danyella Gessyca Reinaldo (Universidade Federal Rural do Semi-Árido, 2018)
Problem structuring methods and methods of support for multicriteria decision making can support more efficient decision making by managers. For this reason, many papers are based and use these methods for more efficient decision making. Thus, this work aims to carry out a literature review of works on Methods of structuring problems. The study justifies the study of the importance of problem-solving methods for decision-making. This paper seeks to review the literature on these methods, so that the results will serve as a basis for future research and more effective decision making. The method used in this work is a quantitative research with qualitative approach in works published between 2008 and 2018. The results show how each method has its particularities and how its application may vary depending on the situation. From this review it was possible to identify the tendencies and gaps in the literature, offering interested parties guidance for future applications and / or improvements.
Monografia
Keywords: Tomada de decisão; Revisão de literatura; Métodos de estruturação de problemas; Apoio à tomada de decisão; Decision making; Literature review; Methods of structuring problems; Support for decision-making; ENGENHARIAS::ENGENHARIA DE PRODUCAO